In silico identification, high yielding isolation and in vitro validation of 6β-cinnamoyl-7β -hydroxyvouacapen – 5α - ol as a Wnt/β-catenin pathway targeted anti-cancer secondary metabolite of Caesalpinia pulcherrima - Nirwani N. Seneviratne; Tolulope P. Saliu; Fathima T. Muhinudeen; Sanadie D. Gamage; Prabudhi S. Garusinghe; Damith Chathuranga; Vinoda D. Athukorala; Ashein Kothalawala; Asirini H. Jayasekara; Rajitha K. Rathnayaka; Umanda Anjalee De Silva; Mohamed Faries; et al. (PLoS ONE, 2025)
Wnt/β-catenin signaling pathway is frequently dysregulated in cancer stem cells (CSCs), a sub population of cancer cell mass that drives tumor proliferation, metastasis, recurrence, and chemoresistance. Despite its therapeutic significance, no clinically approved drugs specifically target this pathway. In the present study, secondary metabolites of the medicinal plant Caesalpinia pulcherrima was computationally screened by molecular docking, dynamics simulation and Molecular Mechanics Poisson-Boltzmann Surface Area (MM-PBSA) based free energy calculations to identify potential inhibitors of β-catenin–Tcf/Lef interaction, a key downstream event essential for Wnt/β-catenin signaling. Diterpene metabolite 6β-Cinnamoyl-7β-hydroxyvouacapen-5α-ol (6βCHV) was identified as a potent inhibitor of the pathway along with four previously reported Wnt/β-catenin pathway inhibitors. To validate the results, bioactivity-guided isolation of major active compound was performed using NTERA-2 cells as a cancer stem cell (CSC) model. The isolated compound was spectroscopically characterized and confirmed to be 6βCHV. Anti-proliferative activity assays revealed that 6βCHV suppressed proliferation of breast cancer stem cells (bCSCs) (IC₅₀ = 49.18 µM), NTERA-2 cells (IC₅₀ = 8.92 µM), and highly Wnt-dependent cancer types, including gastric adenocarcinoma (IC₅₀ = 1.90 µM), hepatocellular carcinoma (IC₅₀ = 5.96 µM), and ovarian carcinoma (IC₅₀ = 7.66 µM). 6βCHV upregulated the tumor suppressor gene, p53 while downregulating Wnt target genes, Cyclin D1 and CD44 leading to apoptosis in bCSCs as confirmed by Caspase 3/7 activation. These findings establish 6βCHV as the principal anticancer compound in C. pulcherrima , exerting its effects, at least in part, through Wnt/β-catenin pathway inhibition.